Fiqih Thaharah Pandangan Ustadz Abdul Somad Mengenai Bewudhu di Toilet - Ramadon, Muhammad; Padlah, Ummul; Latifa, Anida Ummu; Satra, Alihan (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
The command regarding wudu (ablution) was revealed simultaneously with the command to perform prayer (salah). Wudu serves as a fundamental prerequisite for the acceptance of one’s acts of worship. It offers numerous benefits, both spiritually and physically. Therefore, learning the fiqh (Islamic jurisprudence) of wudu is strongly emphasized for Muslims, in order to understand the various issues that may arise in daily life. One of the recurring issues in society is the practice of performing wudu in the toilet. Toilets are generally considered unclean places and are believed to be dwellings of evil spirits (shayatin). Thus, performing a purification ritual such as wudu in such a place seems contradictory—wudu aims to purify, yet it is carried out in a location perceived as impure. This issue requires an in-depth examination, particularly to explore the views of scholars and to compare different scholarly opinions. A prominent Indonesian scholar whose views are considered authoritative in matters of fiqh al-taharah (jurisprudence of purification) is Ustaz Abdul Somad (UAS). This study investigates various sources that present Ustaz Abdul Somad’s perspectives, one of which is his lecture series available on YouTube. The YouTube channel titled “Ustadz Abdul Somad Official” provides accessible explanations on this matter. In one of his Q&A sessions with the congregation, Ustaz Abdul Somad delivered a comprehensive and clear explanation regarding the permissibility of performing wudu in a toilet. His explanation was based on prophetic traditions (hadith) and narrations regarding whether or not the Prophet Muhammad (peace be upon him) had engaged in similar practices.According to the response provided, the Prophet Muhammad SAW permitted performing wudu in a toilet. However, he emphasized the importance of observing proper etiquette while in such a place, including the prohibition of verbally reciting the basmalah (the phrase "Bismillah") aloud within the toilet area.